Optimization Correction Strength Using Contra Bending Technique without Anterior Release Procedure to Achieve Maximum Correction on Severe Adult Idiopathic Scoliosis - Ahmad Jabir Rahyussalim; Ifran Saleh; Dyah Purnaning; Tri Kurniawati (Case Reports in Orthopedics)
Adult scoliosis is defined as a spinal deformity in a skeletally mature patient with a Cobb angle of more than 10 degrees in the coronal plain. Posterior-only approach with rod and screw corrective manipulation to add strength of contra bending manipulation has correction achievement similar to that obtained by conventional combined anterior release and posterior approach. It also avoids the complications related to the thoracic approach. We reported a case of 25-year-old male adult idiopathic scoliosis with double curve. It consists of main thoracic curve of 150 degrees and lumbar curve of 89 degrees. His curve underwent direct contra bending posterior approach using rod and screw corrective manipulation technique to achieve optimal correction. After surgery the main thoracic Cobb angle becomes 83 degrees and lumbar Cobb angle becomes 40 degrees, with 5 days length of stay and less than 800 mL blood loss during surgery. There is no complaint at two months after surgery; he has already come back to normal activity with good functional activity.